2005
DOI: 10.1007/s00198-005-1990-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of 1.25 vitamin D3 deficiency, disease activity and low bone mass in ankylosing spondylitis

Abstract: Vertebral fractures due to osteoporosis are a common but frequently unrecognized complication in established ankylosing spondylitis (AS). It is known that inflammatory activity in rheumatic diseases (i.e., proinflammatory cytokines) itself plays a possible role in the pathophysiology of bone loss. The aim of this study was to analyze whether inflammatory activity and an alteration of the vitamin D metabolism play a substantial role in the loss of bone mass in AS. In this cross-sectional study, 58 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 30 publications
5
63
1
2
Order By: Relevance
“…There are other studies which also showed the same relationship between disease activity parameters (ESR, CRP levels and BASDAI) and bone density indicating that bone loss in AS is predominantly the consequence of inflammatory mediators' action [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 85%
“…There are other studies which also showed the same relationship between disease activity parameters (ESR, CRP levels and BASDAI) and bone density indicating that bone loss in AS is predominantly the consequence of inflammatory mediators' action [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 85%
“…While several studies had shown the aggravating effect of vitamin D's deficiency in the activity markers of AS disease [61][62][63][64] , other studies have not found any correlation [65][66][67] . Although, there is evidence for increased risk of AS in people with deficiency of vitamin D [68][69][70] further studies are required to clarify the causal relationship between the deficiency of vitamin D and activity of AS disease.…”
Section: Vitamin D and Severity Of Asmentioning
confidence: 91%
“…Additionally, Hmamouchi et al in another study, with 653 axSpA patients, mentioned that 25(OH)D had a significant inverse correlation with AS disease activity score, using CRP and Bath Ankylosing Spondylitis Metrology Index (BASMI) 73 . In studies that examined the relationship of 1,25(OH) 2 D with disease activity markers, found a significant inverse correlation between 1,25(OH) 2 D and ESR, BASDAI and CRP 63,64 . In contrast, there are studies that indicated that there is no correlation between 25(OH)D and disease activity [74][75][76] .…”
Section: Therapeutic Effect Of Vitamin D Supplementation In Asmentioning
confidence: 99%
“…Therefore, factors affecting the immune system may have effects on the disease course. One of these factors affecting the immune system is vitamin D. 2 The relationship between serum vitamin D levels and disease activity scores in patients with AS has been studied in a number of studies [3][4][5] with varying results. Based on this controversy, we aimed to elucidate the relationship between serum vitamin D levels and disease activity scores in AS patients as well as to compare vitamin D levels of AS patients with healthy individuals.…”
mentioning
confidence: 99%
“…There was no significant correlation between vitamin D levels and BASDAI scores (r= -0.035, p=0.765). Although the relationship between serum vitamin D levels and disease activity in AS has been studied in a number of studies, [3][4][5] only one study showed a relationship between 25-OH-D levels and disease activity. 4 Lange et al 5 reported a correlation between disease activity in AS and 1,25-OH-D metabolites levels; however, not with 25-OH-D. We used 25-OH-D which is the major circulating form of vitamin D.…”
mentioning
confidence: 99%